2022
DOI: 10.3390/healthcare10112153
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Orthodontic Treatment Need on Oral Health-Related Quality of Life among 12–18-Year-Old Adolescents in Riyadh

Abstract: This study assessed the prevalence of orthodontic treatment needs and oral health-related quality of life (OHRQoL) in 12–18-year-old adolescents and explored the association between OHRQoL and treatment needs, gender, education level and family income. A total of 243 participants with no prior history of orthodontic treatment were included in this cross-sectional study utilizing a standardized self-explanatory questionnaire and clinical examination. The questionnaire consisted of two parts. The first part incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…24,25 In Figure 5, the description of the research trend in the fourth decade continued to focus on the use of the IOTN. [26][27][28][29] as well as numerous articles addressing the relationship between malocclusion or orthodontic care needs and self-esteem and quality of life. Malocclusion may have a negative impact on the patient's psychological condition and quality of life, including self-esteem and selfimage, in addition to its physical effects.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In Figure 5, the description of the research trend in the fourth decade continued to focus on the use of the IOTN. [26][27][28][29] as well as numerous articles addressing the relationship between malocclusion or orthodontic care needs and self-esteem and quality of life. Malocclusion may have a negative impact on the patient's psychological condition and quality of life, including self-esteem and selfimage, in addition to its physical effects.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion affects quality of life, and studies have shown a positive correlation between oral health related quality of life (OHRQoL) and malocclusion. 1 Studies have found that Grade 4 Index of Orthodontic Treatment Need-Dental Health Component (IOTN-DHC) highly influences OHRQoL 2 and that patients who seek orthodontic treatment experience an improvement in overall quality of life. 3 Children in middle school spend most of their time with teachers and parents, and orthodontic awareness among these groups can help in identifying developing malocclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion is an important and prevalent oral health problem worldwide [ 38 , 39 ] and has a negative impact on OHrQoL [ 40 , 41 ]. However, at present, there are no data from studies available that have evaluated the impact on OHrQoL in stage IV periodontitis with pathological tooth migration.…”
Section: Introductionmentioning
confidence: 99%